Investigation of ternary subsystems of superalloys by thin-film combinatorial synthesis and high-throughput analysis - König, Dennis; Pfetzing-Micklich, Janine; Frenzel, Jan; Ludwig, Alfred (MATEC web of conferences, 2014)
A Co-Ti-W thin film materials library was fabricated by magnetron sputtering. By using automated high-throughput measurement techniques (resistance mapping, automated XRD measurements) and cluster analysis a yet unknown phase region was revealed. The existence region of the new ternary phase is close to the composition Co60Ti15W25. In order to transfer the results from thin film to bulk material, a bulk sample was prepared by arc melting and subsequent heat treatment. Scanning electron microscopy and chemical micro-analysis data support that a yet unknown ternary phase exists in the system Co-Ti-W.